Cyclodextrin inclusion complexes of the antihyperlipidemic drug clofibric acid - Mino R. Caira; Susan A. Bourne; Eino N. Mvula (ՀՀ ԳԱԱ հրատ.)
The products of the inclusion of clofibric acid, an antihyperlipidemic, in B-CD(TRIMEB), were investigated by thermal analysis and single crystal X-ray diffraction.
Keywords: Biology; Biochemistry; Pharmacology